2015
DOI: 10.1177/0003489415575055
|View full text |Cite
|
Sign up to set email alerts
|

Massively Parallel DNA Sequencing Successfully Identified Seven Families With Deafness-Associated MYO6 Mutations

Abstract: MPS is powerful tool for the identification of rare causative deafness gene mutations, such as MYO6. The clinical characteristics noted in the present study not only confirmed the findings of previous reports but provided important new clinical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 29 publications
5
38
0
Order By: Relevance
“…This was quite similar to a study evaluating a Caucasian population . Four variants of MYO6 were detected among Japanese deaf subjects and they showed diverse audiogram configurations, including flat and high‐frequency involved with mostly mild to moderate degree HL, except one profound HL patient who eventually received a cochlear implant (CI) . Regarding DFNA22 in Koreans, seven variants of MYO6, including this study, were reported to date, and one variant (c.614G > A, p.R205Q) was shared with a Japanese DFNA22 subject.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This was quite similar to a study evaluating a Caucasian population . Four variants of MYO6 were detected among Japanese deaf subjects and they showed diverse audiogram configurations, including flat and high‐frequency involved with mostly mild to moderate degree HL, except one profound HL patient who eventually received a cochlear implant (CI) . Regarding DFNA22 in Koreans, seven variants of MYO6, including this study, were reported to date, and one variant (c.614G > A, p.R205Q) was shared with a Japanese DFNA22 subject.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, 60% of our DFNA22 cohort from our institute had a nonsense variant (c.613C > T, p.R205X) occurring at the p.R205 residue. This residue was also previously reported in association with a pathogenic missense variant of p.R205Q in both Korean and Japanese cohorts, of which, a pathogenic effect on actin‐activated ATPase activity was functionally shown . This raised the possibility that this site is susceptible to mutational pressure and thus can be a mutational hotspot rather than a founder allele.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations